Assessing QoE-driven management policies for VoIP and Video Streaming service provisioning - Ciambrone, D.; Tennina, S.; Boschi, M.; Tsolkas, D.; Pomante, L. (2018 IEEE 23rd International Workshop on Computer Aided Modeling and Design of Communication Links and Networks (CAMAD), 2018)
In the frame of the CASPER project, we envision the performance evaluation of the new user-centric network and service management for future mobile networks. This paper extends our previous contribution on this subject by detailing a novel system level simulator built upon SimuLTE/OMNeT + + to assess quality of experience (QoE)-aware management policies in real LTE networking conditions with Voice over IP and video streaming traffic patterns. The results demonstrate that an accurate choice of the design parameters both at the application layer and at the network layer is paramount to achieve acceptable QoE levels over the time.